PERILAKU IBU DALAM PEMENUHAN NUTRISI PADA BALITA DENGAN STUNTING - susanty, ade (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: to identify the behavior of mother in providing nutrition for toodler at risk of stunting Methods: This research uses a quantitative descriptive design. Sampling was purposive sampling. Data collection techniques were carried out using observation and questionnaires. to determine the mother's behavior in fulfilling nutrition during pregnancy and breastfeeding. Results: The research results showed that the majority of mothers aged 20-35 years (48.94%). The majority of mothers' education was high school (59.58%), their occupation was as a housewife (80.86%). The nutritional status of children under five found that stunting was more common at the age of 1-2 years (29.79). The behavior of fulfilling maternal nutrition during pregnancy found that the majority of mothers washed their hands before eating and after going to the toilet (100%), and the lowest was the milk consumption of pregnant women (6.38%). The highest maternal behavior when breastfeeding is consuming nutritious food during breastfeeding (95.75%), and continuing to breastfeed until the age of 2 years (91.49%) and the lowest is giving MPASI with snacks between meals (17.02% ) Conclusion: Mother's behavior in fulfilling nutrition during pregnancy is good in maintaining cleanliness, but consumption of pregnant milk is still very low. During the breastfeeding period, the mother has consumed nutritious food and provided breast milk for up to 2 years, but it is still very low to fulfill the complementary foods for breast milk schedule.